Psikologi Agama di Era Modern : Tantangan Dan Peluang Dalam Memahami Pengalaman Keagamaan Kontemporer - Sayyid Rissaldi; Ahmad Badawi; Muhammad Degham Al Fatir; Yuminah Yuminah (Jurnal Budi Pekerti Agama Islam, 2025)
This paper examines problems of religious dialogues in this contemporary era. The conclusion of this discussion suggests that religious dialogue is one of the important problems in the globalization era that becomes one of the alternative methods to anticipate religious conflicts in our society. There are many barriers to develop religious dialogues, such as the level o f knowledge, social-political problems, and psychological and theological barriers. In the recent era, three models of religious dialogue can be developed, that is, theological dialogue, anthropological dialogue, and cosmological dialogue.